Relationship between HCMV and Diabetic Mellitus Type 2 of Elderly Patients in Al-Najaf Governorate - Elham Jawad Kadhum (Journal of Global Pharma Technology, 2016)
The sudden rise mellitus (DM2) and related complications go along with increasing evidence of clinically major age and gender differences. The aim of current study was to study the relationship between the virus and diabetes mellitus type2 through detection of human cytomegalovirus (HCMV) infection in DM2 patients in Najaf governorate by detection of human cytomegalovirus DNA in blood samples by using of PCR technique. Blood samples were collected from 93 diabetic patients randomly. Regarding PCR technique, the study showed that among 93 diabetic patients gave positive results in 39 patients(42%); In contrast, in control group PCR positive result was only 4.4% (4 out of 90) with significant differences . This study concluded that the higher prevalence of HCMV DNA in DM2 patients comparing with normal individuals, which means that patients with DM2 were at high risk for HCMV infections.Keywords: HCMV, DM2, PCR.